How Has Islamic Banking Windows Research Evolved? A Bibliometric Analysis of Trends, Influencers, and Sustainability Linkages - Apriantoro, Muhamad Subhi; El Ashfahany , Afief; Tanasya , Nasya; Puspa , Fina Nusa (Suhuf: International Journal of Islamic Studies, 2025)
This study aims to provide a comprehensive bibliometric analysis of Islamic Banking Windows (IBWs) and their potential role in advancing sustainable finance. By examining publication trends, influential contributors, and research themes, the study seeks to bridge the gap in understanding how IBWs align with environmental, social, and governance (ESG) principles and contribute to global sustainability goals. A bibliometric analysis was conducted using data extracted from the Scopus database, focusing on publications related to Islamic Banking Windows. The study employed co-occurrence network analysis, citation metrics, and productivity indicators to map research trends, identify key contributors, and analyze prevalent themes. The analysis reveals a growing interest in IBWs, particularly in Muslim-majority countries like Malaysia and Indonesia, as well as emerging contributions from Western nations. Key themes include efficiency, customer behavior, Shariah governance, and comparative performance between Islamic and conventional banks. However, the integration of sustainable finance principles remains underexplored, highlighting a critical research gap. The study identifies influential journals and authors, with findings suggesting that IBWs have significant potential to promote ethical and sustainable financial practices. This study is among the first to systematically examine the intersection of IBWs and sustainable finance using bibliometric methods. It provides a structured overview of the field’s evolution, influential works, and emerging trends, offering valuable insights for researchers, policymakers, and practitioners seeking to align Islamic finance with global sustainability agendas.